Efek Pendidikan Kesehatan terhadap Pengetahuan Lansia dalam Pencegahan Kolestrol - Rismawati, Rismawati (Mando Care Jurnal, 2024)
Prevention of cholesterol can be carried out for all individuals with cholesterol issues. Several natural, safe, and effective ways to reduce cholesterol levels include consuming cholesterol-lowering foods, exercising regularly, reducing sugar intake, avoiding smoking, limiting alcohol consumption, managing stress, and taking additional cholesterol-lowering supplements. The purpose of this study is to determine the relationship between health education and elderly knowledge regarding cholesterol prevention. The research method used is a quasi-experimental design. The population in this study consisted of 40 elderly individuals in Karampuang Village, with a total sampling technique used to select all 40 participants. Data were analyzed using a paired test to determine the p-value. Before receiving health education, the majority of the elderly participants (57.5%) had poor knowledge, and none were categorized as having good knowledge. After health education, 85.0% of the participants reached the good knowledge category, while the moderate knowledge category decreased to 15.0%, and no participants remained in the poor knowledge category. Health education significantly improved the level of knowledge among the elderly regarding cholesterol prevention.